The clinicopathological and radiological features of unilateral nasal mass in adults, a tertiary hospital experience - Aljafar, Hadeel M.; Alenazi, Eman R.; Alkhatib, Abdulrahman M.; Alazzeh, Ghaleb M.; Almomen, Ali A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aim and objectives of the study were to analyze and study the diverse presentations of unilateral nasal mass and to identify the suggestive features of neoplastic pathology in adult’s population at a tertiary referral hospital. Methods: A retrospective analysis of 90 patients presented with unilateral sinonasal mass, reported to the Rhinology and Skull Base Clinic at the department of ENT in King Fahad Specialist Hospital, Dammam. The parameters include patient history, clinical assessments and histopathological examinations, which were supplemented with radiological investigations.In addition, demographic information and histopathological examinations for patients, who underwent surgical excision was analyzed for correlation with clinical diagnosis. Results: The reported cases are 55 males and 35 females with a median follow-up period of 12 months, ranging from 2-72 months. Nasal obstruction is the major symptom 34 (38%), 25 (27.8%) cases were reported with nasal mass and clinical diagnosis indicates 18 (20%) cases of malignancy. Type of disease and gender demonstrates low significance (p=0.023), whereas the diagnosis with age is highly significant (p=0.005). Conclusions: Carcinoma, inflammatory polyposis, inverted papilloma and allergic fungal sinusitis were the highest histological diagnosis. The clinical diagnosis and the suggestive features of radiological findings mostly resembled the histological findings. In contrary to the resemblance, the histological finding reveals the general diagnosis of nasal mass to the precise diagnosis, especially the fatal conditions like carcinoma. The high rate of malignancy and its suggestive radiological findings indicates that the specialists should consider the cases with caution to carryout histological analysis to rule out the probability of neoplasm.